The Role of Emotional Intelligence in Environmental Leadership and Policy Negotiation - Adel Subhe Abedalkader Abraheem; Raad Hameed Kambash; Shahd Nasser Saadi Hassan; Abdulrazzaq Tuama Hawas; Ghanim Magbol Alwan (Environment and Social Psychology, 2025)
Environmental leadership and policy negotiation demand the capacity to process emotions, build consensus and negotiate complex stakeholder dynamics. Building on the framework of the Emotional Intelligence (EI), this study analyzes the influence of EI on leadership effectiveness in environmental governance within the context of stakeholder engagement, conflict resolution and policy success. Utilizing a mixed-methods multi-phased approach, the study combines survey analysis, case studies, regression modeling, and structural equation modeling (SEM) to determine the relationship between EI competencies and leadership outcomes. This is particularly insightful for philanthropy and development practitioners, not only because leaders with high EI perform better, especially in stakeholder trust-building, decision-making and policy adoption, but also because these leaders reach better governance outcomes. For EI dimensions Social Skills was the most significant predictor of leadership effectiveness followed closely by Empathy and Emotional Regulation. The article showed that high EI competencies were linked with fewer delays, higher stakeholder satisfaction and better implementation of policies. This study provides practical insight into the value of EI development in leadership training programs to improve collaboration and resilience within environmental decision-making. Additionally, it suggests the need for more research on the long-term effects of EI training, variability of leadership effectiveness across cultures and EI's intersection with emerging technologies in governance. Through its endorsement of the need for emotionally intelligent leadership, this study extends comprehension of the ways in which interpersonal skills affect sustainable environmental policy outcomes. This is particularly insightful for philanthropy and development practitioners, not only because leaders with high EI perform better, especially in stakeholder trust-building, decision-making and policy adoption, but also because these leaders reach better governance outcomes. For EI dimensions Social Skills was the most significant predictor of leadership effectiveness followed closely by Empathy and Emotional Regulation. The article showed that high EI competencies were linked with fewer delays, higher stakeholder satisfaction and better implementation of policies. This study provides practical insight into the value of EI development in leadership training programs to improve collaboration and resilience within environmental decision-making. Additionally, it suggests the need for more research on the long-term effects of EI training, variability of leadership effectiveness across cultures and EI's intersection with emerging technologies in governance. Through its endorsement of the need for emotionally intelligent leadership, this study extends comprehension of the ways in which interpersonal skills affect sustainable environmental policy outcomes.